2015
DOI: 10.1016/j.jrtpm.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

European freight rolling stock fleet size in 2050 in light of the Transport White Paper 2011

Abstract: The European Transport White Paper 2011 sets high modal shift targets from road freight to rail 50% by 2050. The objective of this paper is to determine the rolling stock fleet size and type up to the year 2050 and associated challenges for stakeholders. Considering the White paper targets, three scenarios are considered; a) Business as usual or Reference Scenarioextrapolation of current trends without major policy change; b) White Paper 2011 Low Scenario (WPL) based on a partial implementation of the modal sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Islam and Eidhammer [11] explored Pan-European and international rail freight services. Other recent examples of such a research include CREAM [5], RETRACK [17], Islam et al [14] and Islam et al [13]. The CREAM [5] study, co-funded by the European Commission within the Sixth Framework Programme, contained a number of technological and operational research and development activities identified by the stakeholders, who comprised rail infrastructure operators, railway operators, intermodal operators and their customers.…”
Section: Literature Review On International Freight Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Islam and Eidhammer [11] explored Pan-European and international rail freight services. Other recent examples of such a research include CREAM [5], RETRACK [17], Islam et al [14] and Islam et al [13]. The CREAM [5] study, co-funded by the European Commission within the Sixth Framework Programme, contained a number of technological and operational research and development activities identified by the stakeholders, who comprised rail infrastructure operators, railway operators, intermodal operators and their customers.…”
Section: Literature Review On International Freight Transportmentioning
confidence: 99%
“…The RETRACK [17] study, co-funded by the European Commission within the Sixth Framework Programme, aimed to contribute to the Commission's aspirations of a modal shift of freight traffic from road to rail with a market share of 15 % by 2020 to achieve a commercial viability and contribute to sustainable mobility. Islam et al [13] conducted research to determine future (2030 and 2050) fleet size and found, among others, that significantly more rolling stock (in particular flat wagons, covered wagons and covered hopper wagons) as well as improved asset utilisation would be vital to facilitate the transport of increased freight volume as required in the EU Transport White Paper 2011 European Commission [8]. Another important aspect of international railway freight transport was examined by Islam et al [14].…”
Section: Literature Review On International Freight Transportmentioning
confidence: 99%